2000
DOI: 10.1074/jbc.275.16.12023
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Phosphatidic Acid Synthesis Alters the Structure of the Golgi Apparatus and Inhibits Secretion in Endocrine Cells

Abstract: In mammalian cells, activation of a Golgi-associated phospholipase D by ADP-ribosylation factor results in the hydrolysis of phosphatidylcholine to form phosphatidic acid (PA). This reaction stimulates the release of nascent secretory vesicles from the trans-Golgi network of endocrine cells. To understand the role of PA in mediating secretion, we have exploited the transphosphatidylation activity of phospholipase D. Rat anterior pituitary GH3 cells, which secrete growth hormone and prolactin, were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
107
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 73 publications
(81 reference statements)
13
107
1
Order By: Relevance
“…Several PI kinases and phosphatases are located on the ER, but the exact role that they play in secretion, if any, is not known (224,389,392). Membrane traffic between the ER and Golgi is inhibited when PtdOH production by PLD is blocked (21,322), but it is not clear if this is an effect on the ER or the Golgi.…”
Section: F Phosphoinositides On the Ermentioning
confidence: 99%
See 1 more Smart Citation
“…Several PI kinases and phosphatases are located on the ER, but the exact role that they play in secretion, if any, is not known (224,389,392). Membrane traffic between the ER and Golgi is inhibited when PtdOH production by PLD is blocked (21,322), but it is not clear if this is an effect on the ER or the Golgi.…”
Section: F Phosphoinositides On the Ermentioning
confidence: 99%
“…Golgi membranes isolated from cells overexpressing PLD 1 show elevated production of PtdIns(4,5)P 2 (294), consistent with stimulation of a PIP5KI enzyme by PA. In a series of studies, Shields and colleagues (322,323,346) have shown that PtdIns(4,5)P 2 is required to maintain Golgi structure and its production is regulated through the production of PA. Overexpression of a dominant negative PI4KII␤ disrupts the structure of the Golgi, perhaps by interfering with the ability of spectrin to bind to membranes (120), although it is not clear if this is due to the lack of a precursor for PtdIns(4,5)P 2 or to a direct effect of insufficient PtdIns(4)P. The release of secretory vesicles exporting hormones from the TGN requires PtdIns(4,5)P 2 (42,324). The nature of the vesicle coat, if any, involved in this transport step is not known.…”
Section: E Ptdins(4)p and Ptdins(45)p 2 On The Golgimentioning
confidence: 99%
“…However, PLD1 overexpression failed to increase the number of ␤APP-containing vesicles budded from the TGN in PS1 Ϫ/Ϫ fibroblasts, probably because of a maximal rate of ␤APP-containing vesicle trafficking in PS1-null cells. Inhibition of PLD1 catalytic activity by 1-butanol (an inhibitor of PLD-catalyzed formation of PA) (11,16), resulted in decreased ␤APP trafficking from the TGN in both PS1wt and PS1 Ϫ/Ϫ cells (Fig. 1b).…”
Section: Pld1mentioning
confidence: 99%
“…For the preparation of PS or PA, 14 C-labeled PC was suspended in 500 l of diethylether, and then 500 l of a solution comprising 100 mM sodium acetate, pH 5.5, 100 mM CaCl 2 , and 5 M L-Ser was added. The reaction was started by the addition of 2.5 units of Actinomadura phospholipase D (Meito Sangyo, Tokyo, Japan), and 2.5 units of phospholipase D was added every 15 min.…”
Section: C-labeled Substrates-1-[1-mentioning
confidence: 99%
“…Several lines of evidence suggest that PA is also involved in vesicle-mediated transport and Golgi organization (11)(12)(13)(14). Recent elegant studies demonstrated that the conversion of lyso-PA, an inverted cone-shaped lipid, to PA, a cone-shaped lipid, induces fission of vesicles from the plasma membrane (15) or tubulation of the Golgi apparatus (16).…”
mentioning
confidence: 99%